PANDANGAN WAHBAH AZ-ZHUHAILI TERHADAP MAKNA MENSTRUASI DITINJAU DARI PERSPEKTIF FEMINISME - Monica Mulyana (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This study aims to provide problem solving and scientific information to the general public and especially women who take part in the public and domestic spheres on issues regarding menstruation from Wahbah az-Zhuhaili's view in Tafseer al-MunÄ«r from the perspective of Feminism. The method used in this study is library research. The sources used are primary sources, namely Tafseer al-MunÄ«r as a material object, and criticism of feminism as a formal object, while the secondary sources are journals, books, commentaries, websites, and other sources that support this research. This method uses content analysis method which is carried out with critical thinking. The results of this study indicate that menstruation (mahidh) in Surah Al-Baqarah verse 222, which is interpreted as dirty blood by Az-Zhuhaili, has received criticism from Indonesian Muslim Feminism. According to feminism, menstruation is an adza (disease) that affects the physical and psychological state of women. Then, the conclusion in this study is that feminists consider that Wahbah az-Zhuhaili's view related to menstruation is still textual, judging from his interpretation, az-Zhuhaili tends to take the opinion of classical scholars who should have contemporaries Muslims tend to have a contextual view.